ABDOMINAL RADIOLOGY IN ONCOLOGY: THE NEW TRENDS IN COMPUTED TOMOGRAPHY AND MAGNETIC RESONANCE IMAGING - A. B. Lukiyanchenko; V. E. Sinitsin; V. O. Panov (Вестник рентгенологии и радиологии)
Paper gives a review of recent technical innovations in computed tomography (CT) and magnetic resonance imaging (MRI) that could be applied in abdominal oncology. Perfusion and dualenergy CT gives new opportunities for tissue characterization. Interactive reconstruction algorythms decrease radiation exposure to patients. Abdominal MRI has some important advantages over CT in detection and staging of abdominal malignancies. Nowadays standard MR protocols include DWI and dynamic 3D sequences with extracellular or liver-specific contrast media. Latest developments in MRI technology could expand its diagnostic value in abdominal oncology even further.